1978
DOI: 10.1159/000198139
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Lactic Dehydrogenase Patterns in Carcinoma of Stomach and in Peritumoral Tissues

Abstract: Segments of gastric mucosa from 32 surgical and biopsy specimens containing gastric carcinoma have been studied to determine the total content of lactate dehydrogenase (LDH). The LDH isoenzyme distribution patterns in tumoral tissues have been compared to that of peritumoral tissue and to the gastric mucosa of a healthy control group. LDH isoenzyme activity in the samples from tumoral tissue was significantly increased. The adjacent peritumoral tissue had a slight increment in the polypeptide M as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The authors deemed the altered LDHA to LDHB ratio as a possible biochemical indicator of an early process of malignant conversion [67]. These conclusions were supported by the data of other investigators who showed high LDHA to LDHB ratios in uninvolved tissues from resection edges that were related to local recurrence possibly due to deep infiltration [58,59,[68][69][70][71]. It is known that LDH-5 overproduction is related exclusively to cancer cells but not to stromal fibroblasts, which have low LDHA expression [72].…”
Section: Clinical Significance Of Ldh Isoenzymesmentioning
confidence: 56%
“…The authors deemed the altered LDHA to LDHB ratio as a possible biochemical indicator of an early process of malignant conversion [67]. These conclusions were supported by the data of other investigators who showed high LDHA to LDHB ratios in uninvolved tissues from resection edges that were related to local recurrence possibly due to deep infiltration [58,59,[68][69][70][71]. It is known that LDH-5 overproduction is related exclusively to cancer cells but not to stromal fibroblasts, which have low LDHA expression [72].…”
Section: Clinical Significance Of Ldh Isoenzymesmentioning
confidence: 56%
“…Less frequently, significant changes in the number of LDH-B isoforms are observed. In the case of benign lesions, lactate production is much lower than in malignant tumors, and the percentage of individual isoforms does not differ significantly from that determined in normal tissues from which the lesions originate [68,72]. Although the mechanism regulating the expression of lactate dehydrogenase subunits and the synthesis of active tetramers is unknown, it is known that the ldha and ldhb genes are influenced by separate gene control regions [19][20][21][22][23].…”
Section: Ldh Isoenzymes In Cancersmentioning
confidence: 94%
“…It was also reported that as the distance from the tumor margin increases, the A/B ratio of LDH subunits decreases and it is associated with decreasing relative activity of LD5 and LD4 isoforms, and increasing LD1 and LD2 [17,66]. A number of studies have shown that there is a zone around the tumor in which, despite the lack of visible morphological changes, changes in the activity of LDH isoenzymes are observed [19,20,[66][67][68]. These authors concluded that the reorientation of LDH isoenzymatic activity in histologically normal tissues surrounding the tumor must be due to an impaired metabolic balance reflecting precancerous changes.…”
Section: Ldh Isoenzymes In Cancersmentioning
confidence: 99%